Capabilities-Based Approach to Parameters Selection for Manipulators of Man-Portable Unmanned Ground Vehicles - Tomasz Krakówka; Andrzej Typiak; Rafał Typiak; Maciej Cader (Applied Sciences)
This paper presents a method for designing manipulators for man-portable UGVs (Unmanned Ground Vehicles), intended for military and counter-terrorism applications. The approach involves selecting manipulator parameters based on requirements for capabilities and a database of available components. The authors identified a gap in the existing literature regarding load definition, particularly for small robot manipulators used in Explosive Ordnance Disposal (EOD) tasks. To address this, a method is proposed consisting of three main stages: In the first stage, manipulator drives and geometric parameters are selected. In the second stage, a detailed load analysis is performed. A distinctive feature of the proposed method is the use of optimization techniques to determine the maximum possible loads during load case definition. In the final stage, topological optimization of the components is carried out. The method was validated using a selected manipulator joint of a portable robot designed for EOD tasks.